Mendelian and non-Mendelian quadratic operators - Ganikhodjaev, Nasir; Saburov, Mansoor; Jamilov, Uygun (Natural Publishing, 2013)
In this paper, we attempt to provide mathematical models of Mendelian and Non-Mendelian inheritances of the bisexual population system having Fisher’s 1:1 principle. In our model, we always assume that distributions of the same phenotype of female and male populations are equal. We study the evolution of a Mendelian trait. As an application of a non-Mendelian inheritance, we construct a quadratic stochastic operator that describes transmission of ABO and Rh blood groups.